2006
DOI: 10.1007/s11136-006-0049-1
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual equivalence and health-related quality of life: an exploratory study in Japanese and Dutch cancer patients

Abstract: Research into the equivalence of Western and Japanese conceptualizations of health-related quality of life (HR-QOL) is scarce. We used the Western (European Organization for Research and Treatment of Cancer, EORTC-QLQ-C30) and the Japanese questionnaire in order to analyze the conceptual similarity of HR-QOL factors, and the associations between specific symptom items with overall HR-QOL in Japanese (n=265) and Dutch (n=174) patients with various types of cancer. Both populations completed both instruments. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
0
9
0
1
Order By: Relevance
“…determine the emotional response to cancer, participation in screening, use and compliance with treatment, and the relationship between health professionals and patients" (p. 123). In earlier studies we found that Japanese and Dutch patients with various types of cancer (breast, colon, lung, prostate) responded in a quite similar way to a fairly large set of QOL questionnaires; differences were found mainly on the social dimensions of QOL Kleijn et al, 2006).…”
Section: Introductionmentioning
confidence: 81%
“…determine the emotional response to cancer, participation in screening, use and compliance with treatment, and the relationship between health professionals and patients" (p. 123). In earlier studies we found that Japanese and Dutch patients with various types of cancer (breast, colon, lung, prostate) responded in a quite similar way to a fairly large set of QOL questionnaires; differences were found mainly on the social dimensions of QOL Kleijn et al, 2006).…”
Section: Introductionmentioning
confidence: 81%
“…Two published articles contrasting the structure of the EORTC QLQ-C30 across multiple cultural/ethnic groups were identified, both based on relatively small samples. One suggested an equivalent factor structure for Caucasians and Asian/Pacific Islanders in Hawaii [7]; another found similar conceptual equivalence of the concept of HRQoL in the Netherlands and Japan [8].…”
Section: Introductionmentioning
confidence: 94%
“…As a consequence, patients’ Quality of Life (QoL) has become one of the main outcomes of treatment. Although Japanese and European cancer patients previously have shown considerable equivalence with regard to the concept of QoL [ 3 ], cross-cultural comparisons between Asian and European breast cancer patient samples have seldom been performed [ 4 ]. One study showed that Japanese women with breast cancer report better physical QoL than German women, but found no difference between countries with regard to emotional well-being [ 5 ].…”
Section: Background and Rationalementioning
confidence: 99%